MAKNA KONOTATIF SYAIR QASIDAH SALAWAT NABI PADA NASKAH MAJELIS DZIKIR DAN SALAWAT PONDOK RUMI UNTUK MAJELIS AL-ASYIQIN JAMBI (KAJIAN SEMANTIK) - Uli Wahyuni; Rini Pujiyanti (Universitas Batanghari, 2019)
The aim of this research is to describe the connotative meaning of solawat nabi qasidah. This research uses qualitative approach by using descriptive method. This research is descriptive qualitative. In this research, the data is taken by collecting whole data, choosing the data, and analyzing the data in concluding section. The data is taken from the words of data source. The source of the data is the texts of solawat nabi qasidah. In collecting the data, the texts of solawat nabi qasidah which are related with connotative meaning are read. Based on the analysis, there are 13 connotative meaning on the texts of solawat nabi qasidah. From those 36 titles, there are 8 titles which consist of connotative meaning. There are more than one connotative meaning from each title. Thus, it can be concluded that the texts of solawat nabi qasidah consist of connotative meaning. Keywords: Connotative Meaning, Solawat Nabi Qasidah